The difference between pulp chamber size of the mandibulary first molar in patient with diabetes mellitus and non diabetes mellitus age 25-34 years using periapical radiography - Syamsiah Syam; Nurasisa Lestari; Rya Sepriani (DiscoverSys Inc., 2020)
Objective: The purpose of this study was to determine the differences size of mandibular molar pulp chamber in patients with diabetes mellitus and non-diabetes mellitus aged 25 to 34 years using periapical radiography.Material and Methods: This study is analytically using the cross sectional observation. The population was patients who suffer from diabetes mellitus and non-diabetes mellitus at Tamamaung Health Center and at the Private General Practitioner Practice in Makassar. The samples was determined according to the inclusion and exclusion criteria in the study. Results: The measurements of this study based on independent t test obtained p value (0.000) <α (0.01) which meansthere was a statistically significant difference of pulp chamber size of the mandibulary first molar teeth patients with diabetes mellitus and non- diabetes mellitus using periapical radiography. Conclusion: The presence of microvascular disorders and atheroma formation in the pulp causes the highest part of the pulp chamber of patients with diabetes mellitus experienced a reduction in size compared to the pulp chamber of non-diabetes mellitus.